Barriers to restoration: Pollution alters nurse effects for an ecosystem engineer. Issue 12 (16th September 2021) - Cameron, Hayley; Amor, Michael D.; Bellgrove, Alecia
Abstract: Nurse plants modify the environment beneath their canopies to create favourable habitats for propagule recruitment. Nurse plants are potentially valuable tools for ecological restoration—yet empirical tests, particularly in polluted environments, remain rare. The few studies that do exist find that nurse plants positively affect propagule recruitment in polluted environments. Yet most tests have focused on pollution‐tolerant species in metal‐contaminated environments. Biotic interactions are highly context dependent, however, such that extrapolations to other suites of species and pollutant types appear premature. We examined changes in intraspecific nurse effects across pollution regimes for a pollution‐sensitive, macroalgal ecosystem engineer that is a target for intertidal restoration. In a manipulative field experiment, we out‐planted propagules in the presence and absence of conspecific canopies at unpolluted control shores and shores that received a partly remediated (low‐toxicity) sewage effluent. We then monitored the performance (survival and growth) of these propagules over time. Algal canopies facilitated the survival and early growth of propagules at control sites, but not at partially remediated sites where propagules performed poorly irrespective of canopy presence. Synthesis and applications . Using a pollution‐sensitive, macroalgal ecosystem engineer, we show for the first time that nurse‐plant effects can be contingent on pollution regime, and that exposure to pollution (even at low levels) can erode nurse effects. We caution that nurse plants are unlikely to be universal tools for ecological restoration, including systems where facilitative nurse effects naturally occur (in our case, macroalgal canopies on unpolluted rocky reefs). Management practitioners should carefully consider the disturbance (e.g. pollution) tolerance of target species, and test whether nurse effects are maintained under current disturbance regimes, before large‐scale translocations are attempted. Abstract : Using a pollution‐sensitive, macroalgal ecosystem engineer, we show for the first time that nurse‐plant effects can be contingent on pollution regime, and that exposure to pollution (even at low levels) can erode nurse effects. We caution that nurse plants are unlikely to be universal tools for ecological restoration, including systems where facilitative nurse‐effects naturally occur (in our case, macroalgal canopies on unpolluted rocky reefs). Management practitioners should carefully consider the disturbance (e.g. pollution) tolerance of target species, and test whether nurse effects are maintained under current disturbance regimes, before large‐scale translocations are attempted.